Factors and consequences of acid rain incidence - Leal , Ranavalo de Araújo; Silva, Tallys Antonio da; Mergulhão, Thiago José Cavalcanti; Monteiro, Eliana Cristina Barreto; Takaki , Galba Maria Campos (Seven Editora, 2023)
In the mid-seventeenth century in England, at the epicenter of the Industrial Revolution, due to high air pollution, observations were initiated on rainfall with acid content that harmed ecosystems. With industrial advancement on a global scale, acid rain has become frequent in many parts of the world. Acid rain results from chemical reactions, mostly mediated by anthropogenic actions such as industrial activities that cause the emission of sulfur dioxide (SO2) and nitrogen oxide (NOx) into the atmosphere, and produce strong acids such as sulfuric acid (H 2SO4) and nitric acid (HNO3). These cause various damages to human health as well as damage to the air, in the aquatic environment, attacking the soils, agriculture, buildings, and monuments. There are several international and national instruments to regulate guidelines that prevent polluting activities and thus try to mitigate the negative effects of acid rain, the most recent being the Sustainable Development Orders (SDGs). Despite the existing policies, it is necessary to impose more on sustainable regiments and to encourage research on the subject so that, together, it acts more severely against the effects of acid rain around the world. This research presents the concept of acid rain, exposure to risk factors, consequences, and reflections on the challenges of managing acid rain. DOI:https://doi.org/10.56238/alookdevelopv1-062